Religion and the Life-World - Sławkowski-Rode, Mikołaj (Eidos. A Journal for Philosophy of Culture, 2024)
Preview: This special issue of Eidos. A Journal for Philosophy of Culture follows on from the double special issue on Science and Religion published at the end of last year. This double issue focused primarily on questions in metaphysics and ontology. What several of the contributions have pointed out, however, is that the naturalistic worldview, which takes empirical science to be the only reliable source of knowledge, also implies a certain approach to living. Unsurprisingly this outlook extends beyond epistemological commitments of naturalism and has consequences for the fundamental values which guide some of our choices and shape our outlook on the world. Being critical of this trend Roger Scruton has called it the charm of, or enchantment with, disenchantment.